2014
DOI: 10.1038/srep03767
|View full text |Cite
|
Sign up to set email alerts
|

Reduced erythrocyte deformability associated with hypoargininemia during Plasmodiumfalciparum malaria

Abstract: The mechanisms underlying reduced red blood cell (RBC) deformability during Plasmodium falciparum (Pf) malaria remain poorly understood. Here, we explore the possible involvement of the L-arginine and nitric oxide (NO) pathway on RBC deformability in Pf-infected patients and parasite cultures. RBC deformability was reduced during the acute attack (day0) and returned to normal values upon convalescence (day28). Day0 values correlated with plasma L-arginine levels (r = 0.69; p = 0.01) and weakly with parasitemia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…Disruption of erythrocyte NO metabolism by the parasite could contribute to the reduced deformability of the erythrocyte and thereby could inhibit circulation of infected erythrocytes through capillaries. Rey and colleagues recently demonstrated that the deformability of infected erythrocytes is, in part, dependent on exogenous arginine, and hence NO biosynthesis (Rey et al, 2014). The molecular identity of the enzyme(s) involved is yet to be resolved, as is that of the high-affinity transporter, which mediates the uptake of arginine into the parasite, thereby depleting arginine from the host cell compartment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disruption of erythrocyte NO metabolism by the parasite could contribute to the reduced deformability of the erythrocyte and thereby could inhibit circulation of infected erythrocytes through capillaries. Rey and colleagues recently demonstrated that the deformability of infected erythrocytes is, in part, dependent on exogenous arginine, and hence NO biosynthesis (Rey et al, 2014). The molecular identity of the enzyme(s) involved is yet to be resolved, as is that of the high-affinity transporter, which mediates the uptake of arginine into the parasite, thereby depleting arginine from the host cell compartment.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, it was reported that there is, in the parasite, a pool of NO localized to the digestive vacuole (Ostera et al, 2008); however, no citrulline production was detected, and it was proposed that the parasite's NO pool is maintained not by a NOS but by the ingestion of host cell cytosol and the subsequent conversion of host nitrate to NO by an unknown parasite nitrate reductase (Ostera et al, 2008;Ostera et al, 2011). By contrast, Rey and colleagues reported that there to be an NO pool present throughout the parasite, sustained by an arginine-dependent pathway (Rey et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Plasmodium falciparum produces an arginase resulting in hypoargininemia, decreasing the bioavailability of nitrogen atoms for nitric oxide synthesis by erythrocytes. This decreases the deformability of both parasitized and unparasitized erythrocytes [32]. Malarial infection also causes extensive remodeling of the erythrocyte cell membrane, which decreases its zeta potential, fostering erythrocyte aggregation [33].…”
Section: Review the Association Of Infection With Myocardial Infarctionmentioning
confidence: 99%
“…It was reported that P. falciparum parasites under the pressure of S-nitroso-N-acetyl-penicillamine (SNAP), the NO donor, died by autophagic-like cell death (Totino et al 2008). Another study showed that NO production increased in P. falciparum parasites incubated with L-Arg in vitro (Rey et al 2014). These results suggest that L-Arg supplementation may have a direct effect on the viability of malaria parasites in vivo, and more work needs to be done to prove it.…”
Section: Discussionmentioning
confidence: 99%